A case study on the value of humanities-based analysis, modes of presentation, and study designs for SoTL: close reading students’ pre-surveys on gender-inclusive language - Copland, Sarah (My University, 2023)
Close reading has long been heralded as a humanities-specific methodology with significant potential for SoTL. This essay fills a gap in SoTL literature with a full case study demonstrating what, exactly, close reading shows us about our data that social science-based quantitative and qualitative analyses may not. Close reading-based analysis of first-year writing students’ pre-surveys on gender-inclusive language entails attention to the interrelated form and content of students’ self-reflections. This analysis reveals nuances and complexities that, if overlooked, would result in inadvertent misrepresentation of the data. This case study responds not only to calls for humanities-specific SoTL methodologies but also to related calls for greater legitimation of diverse forms for SoTL dissemination, some of which originate in the humanities. It is therefore cast as a reflective essay based on its author’s scholarly personal narrative (SPN) as a new, humanities-based SoTL researcher. Finally, this case study demonstrates the value of flexible, deliberately unscientific study designs that are responsive to emergent conditions but foreign to SoTL’s dominant social science paradigm. As guides to instruction, pre-surveys are necessary complements to pre-quizzes: learning what students think they know about a concept or skill, their attitudes towards it, and their contexts of prior learning about it—not just their knowledge of it, which is all pre-quizzes can tell us—is an important precursor to effective instruction. But maximizing pre-surveys’ potential to guide instruction requires flexible study designs so we can change our pedagogy, including our study’s “intervention,” if necessary, on the fly.
Keywords: humanities; close reading; gender-inclusive language; pre-surveys; flexible study designs